Peningkatan Workability Pasta Beton Modifikasi Dengan Pemanfaatan Abu Sekam Padi Menggunakan Superplasticizer - Nugraha, Rama Putra; Mahardana, Zendy Bima; Winarto, Sigit (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Infrastructure development in Indonesia is the main focus of the government, especially in the construction sector with toll road projects, airports, high-speed rail lines, and smart cities in the new capital city. Concrete is becoming the main material in infrastructure because of its high compressive strength and relatively low cost. Aggregates, especially natural and artificial, play a key role in concrete structures. The growth in demand for natural aggregates has an impact on environmental damage due to mining. Innovations using Rice Husk Ash instead of natural aggregates emerged as an environmentally friendly solution. However, it is necessary to optimize the mix design and handle workability reduction with superplasticizers. The percentage of superplasticizers used is 0%, 0.52%, 0.54%, 0.56%, 0.58% of the total use of cement. In concrete workability tests, such as Flowability, Passingability, and Viscosity, it was found that a 0.54% SCCRHA mixture showed optimal performance. The Flowability test showed a Slump Flow runoff value of 77.5 cm (SF3 category), while the J-Ring test showed a runoff of 75 cm with 2.5 cm blocking (No Blocking). The Viscositytest showed T-500 and V-Funnel times of 1.8 seconds and 2.18 seconds, respectively, with VF1 and VS1 (good filling) classifications. The results showed that this mixture achieved the most effective design with a compressive strength of 25.17 MPa, showing an increase of 13% compared to the plan mixture